Associations of firearm dealer openings with firearm self-harm deaths and injuries: A differences-in-differences analysis. - Ellicott C Matthay; Kriszta Farkas; Dana E Goin; Kara E Rudolph; Veronica A Pear; Jennifer Ahern (PLoS ONE)
Background Firearm dealer density is correlated with firearm interpersonal violence, but no quasi-experimental studies have assessed whether changes in dealer density lead to changes in firearm self-harm injuries and deaths. We assessed whether openings of firearm dealers are associated with short-term changes in local firearm self-harm injury rates. Methods We identified 718 openings of firearm dealers in California using licensing data, 2014-2016. We defined exposure regions based on aggregations of zip codes defined by proximity to firearm dealer openings and matched each opening to four control regions on time and determinants of firearm injury. We applied a differences-in-differences approach to compare rates of firearm self-harm, in the month before and after each opening, in places with and without openings. Results Firearm dealer openings were not associated with acute, local changes in firearm self-harm relative to places without openings (ratio of rate ratio: 0.90 [95% CI:0.68-1.19]). Results were robust to numerous sensitivity and secondary analyses. Conclusion We found no associations of firearm dealer openings with acute, localized firearm self-harm deaths and injuries. Our focus on acute, local effects; broad availability of dealers and firearms; durability of firearms; or strong confounding-control may explain these null findings.